A conceptual design of vectored water-jet propulsion system - Shuxiang Guo; Xichuan Lin; Hata, Seji (2009 International Conference on Mechatronics and Automation, 2009)
This paper presents a novel vectored water-jet propulsion system which is supposed to be used on a spherical underwater vehicle. This system uses water-jet as its propulsion method and by using servo motors, the direction of output force can be regulated for different propulsion tasks. This paper mainly focuses on the conceptual design of the system. To testify the availability of this design, a physical-based vectored water-jet propulsion system is developed using MATLAB/Simscape. Firstly, the servo motors module and flow rate control module are discussed respectively including modeling and simulation, and then a combined simulation of them is performed.